Increasing the use reliability of a work roll assembly with internal heating by predicting the thermal stress state - Kulik, T. O.; Кулік, Т. О. (ТОВ "ТЕХНІЧНИЙ УНІВЕРСИТЕТ "МЕТІНВЕСТ ПОЛІТЕХНІКА", 2025)
Rolling rolls are one of the decisive factors in the formation of flat-rolled product quality indicators. In order to be able to promptly assess the operational reliability of the roll to ensure stable quality indicators, a model of the temperature-stressed state of work rolls with an internal heating source was developed. Considering that during the hot rolling process, the rolls are characterized by high levels of deforming forces and the presence of elevated temperatures in the deformation zone, a complex stressed state arises in them, caused by the joint action of torques, residual stresses, contact forces, bending moments and thermal loads. Contact stresses exert the maximum impact on the stability of work rolls. The model is based on solving the differential equation of heat conductivity and uses elements of the theory of elasticity. The roll is considered a thick-walled pipe with a symmetric temperature distribution along the longitudinal axis, which is loaded by the full rolling force, the reaction from the support rolls and the temperature loads caused by the temperature mismatch of the inner and outer surfaces. The developed mathematical model solves the problem of determining the thermally stressed state of the working roll, which allows for predicting the operational reliability of the rolls during the rolling process. Thus, the result of the numerical implementation of the model showed that at a certain ratio of the outer and inner radii of the roll, the stresses at the upper point of the axial channel change from relatively safe compressive stresses to more dangerous tensile stresses. Also, the analysis of the results showed that an increase in the diameter of the inner hole leads to a relative decrease in the temperature streses on the surface of the axial hole and a decrease in the temperature stresses on both the outer and inner surfaces of the working roll. In general, the developed mathematical model can be used both for optimizing the design parameters of the roller assembly and for predicting operational use reliability.

Прокатні валки є одним із вирішальних факторів формування показників якості плоского прокату. Для можливості оперативної оцінки їх експлуатаційної надійності з погляду отримання стабільних показників якості готової продукції розроблено модель термонапруженого стану робочих валків з внутрішнім джере лом нагрівання. Ураховуючи, що під час процесу теплої прокатки для валків характерні високі рівні дефор мувальних сил і наявність підвищених температур в осередку деформації, у них виникає складний напру жений стан, викликаний спільною дією обертових моментів, залишкових напружень, контактних сил, згинальних моментів та теплових навантажень. Максимальний вплив на стійкість робочих валків мають контактні напруження. Модель ґрунтується на розв’язанні диференціального рівняння теплопровідності та використовує елементи теорії пружності. Валок розглядається як товстостінна труба із симетрич ним по поздовжній осі розподілом температур, яка навантажена повною силою прокатки, реакцією від опорних валків та температурними навантаженнями, які викликані невідповідністю температури вну трішньої та зовнішньої поверхонь. Розроблена математична модель виконує завдання визначення тер монапруженого стану робочого валка, що дає змогу прогнозувати експлуатаційну надійність валків під час процесу прокатки. Так, результат числової реалізації моделі показав, що за певного співвідношен ня зовнішнього й внутрішнього радіусів валка напруження у верхній точці осьового каналу змінюються з порівняно безпечних напружень стиснення на більш небезпечні напруження розтягування. Також аналіз результатів показав, що збільшення діаметра внутрішнього отвору призводить до відносного зменшення температурних напружень на поверхні осьового каналу та водночас зменшення температурних напру жень і на зовнішній, і на внутрішній поверхні робочого валка. Загалом, розроблена математична модель може використовуватися як для оптимізації конструктивних параметрів валкового вузла, так і для про гнозування показників експлуатаційної надійності.
Підвищення експлуатаційної надійності вузла робочого валка з внутрішнім джерелом нагріву шляхом прогнозування його термонапруженого стану
Keywords: reliability; warm rolling; roll assembly; internal heating; thermal stress state; temperature field; mathematical model; надійність; тепла прокатка; валковий вузол; внутрішній нагрів; термонапружений стан; температурне поле; математична модель